The Influence of Digital Marketing and Brand Trust on Consumer Purchase Interest in the Tokopedia Marketplace (Study on Tokopedia Marketplace Visitors in Surabaya) - Bagas Pambudiantono; Zumrotul Fitriyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of e-commerce is currently being favored by consumers, one of which is Tokopedia. Many advantages are obtained when shopping online. Other things are also obtained, namely, shopping activities become more practical, saving energy and time. Tokopedia experienced a 10% decrease in visitors. In the Top Brand Award, Tokopedia is in second place behind its competitor, Shopee. This study aims to determine the effect of digital marketing and brand trust on purchase intention at Tokopedia. The population in this study is comprised of consumers who have visited and seen advertisements on Tokopedia. The sampling technique used was purposive sampling with a total of 96 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is Partial Least squares (PLS). The results of the study show that Digital Marketing and Brand Trust have a positive and significant effect on Impulse Buying.